Non-obstructive idiopathic pachymeningitis cervicalis hypertrophica. Issue 12 (December 1986) - Kao, K P; Huang, C I; Shan, D E; Ho, J T; Chang, T; Chu, F L
Abstract : Two young men had similar nonobstructive idiopathic pachymeningitis cervicalis hypertrophica, causing chronic (13 and 11 years respectively) C8-T1 radiculomyelopathy proved by surgical and pathological findings. The preoperative Queckenstedt tests and myelography showed no evidence of CSF obstruction. These unusual findings contrast with previous reports which all described complete or at least partial, block. The findings on metrizamide computed tomogram have not been described before. In the two patients it revealed diffuse cord atrophy from C7 to T2 and hemiatrophy with lateral beaking from C4 to C7. The patients benefited from multiple transverse durotomies. The main pathogenesis of the cord atrophy was the compromizing of feeding radicular arteries rather than direct compression.